Enhancing the Protective Immune Response to Administration of a LIVP-GFP Live Attenuated Vaccinia Virus to Mice - Sergei N. Shchelkunov; Stanislav N. Yakubitskiy; Kseniya A. Titova; Stepan A. Pyankov; Alexander A. Sergeev (Pathogens, 2021)
Following the WHO announcement of smallpox eradication, discontinuation of smallpox vaccination with vaccinia virus (VACV) was recommended. However, interest in VACV was soon renewed due to the opportunity of genetic engineering of the viral genome by directed insertion of foreign genes or introduction of mutations or deletions into selected viral genes. This genomic technology enabled production of stable attenuated VACV strains producing antigens of various infectious agents. Due to an increasing threat of human orthopoxvirus re-emergence, the development of safe highly immunogenic live orthopoxvirus vaccines using genetic engineering methods has been the challenge in recent years. In this study, we investigated an attenuated VACV LIVP-GFP (TK-) strain having an insertion of the green fluorescent protein gene into the viral thymidine kinase gene, which was generated on the basis of the LIVP (Lister-Institute for Viral Preparations) strain used in Russia as the first generation smallpox vaccine. We studied the effect of A34R gene modification and A35R gene deletion on the immunogenic and protective properties of the LIVP-GFP strain. The obtained data demonstrate that intradermal inoculation of the studied viruses induces higher production of VACV-specific antibodies compared to their levels after intranasal administration. Introduction of two point mutations into the A34R gene, which increase the yield of extracellular enveloped virions, and deletion of the A35R gene, the protein product of which inhibits presentation of antigens by MHC II, enhances protective potency of the created LIVP-TK--A34R*-dA35R virus against secondary lethal orthopoxvirus infection of BALB/c mice even at an intradermal dose as low as 103 plaque forming units (PFU)/mouse. This virus may be considered not only as a candidate attenuated live vaccine against smallpox and other human orthopoxvirus infections but also as a vector platform for development of safe multivalent live vaccines against other infectious diseases using genetic engineering methods.